A systematic review on the determination and analytical methods for furanic compounds in caramel models - Chan, Ai Chee; Siti Umairah, Mokhtar; Hong, Pui Khoon (Springer, 2025)
Caramelization is the heat-induced transformation of sugars, leading to the formation of characteristic caramel flavours and colours. Furanic compounds such as 5-hydroxymethyl-2-furfural (HMF) and furfural were the intermediate products in this caramelization process. Excessive amounts of HMF, may pose food safety concerns, potentially influence human health. This systematic review aims to elucidate the types of sugar and amino acids that are usually used in previous studies, the type, and quantities of furanic compounds in the caramel model and to explore the diverse quantification methods employed in relevant studies. Preferred Reporting Items for Systematic Reviews and Meta-Analyses(PRISMA)method was employed in this study. Employing keywords such as “caramel”, “caramelization”, “browning”, “furanic”, “furfural”, “furan”, and “hydroxymethylfurfural” were used. A total of 1303 papers were obtained from the initial search by using Web of Science and Scopus database. Finally, 21 papers were selected after being evaluated. The results showed glucose and lysine were the most employed sugar and amino acids to develop caramel and Maillard reaction model in the previous studies. HMF emerged as the prevalent furanic compound, closely followed by furfural and 5-methylfurfural. These three furanic compounds contribute to the bitter taste of the caramel model. High Performance Liquid Chromatography (HPLC) is the preferred method for furanic compound analysis due to the low melting point and polar properties of furanic compounds. Other quantification methods include Solid-Phase Microextraction Gas Chromatography Mass Spectrometer (SPME GC-MS) and spectroscopy methods. This paper summarises furanic chemical analysis in caramel models, including existing understanding and methodological trends.